PMM.21 Antenatal Haemoglobin Levels and Blood Transfusion. (9th June 2014) - Everett, L; Wainwright, S; Ciantar, E
Abstract : Background and Aims: This study investigates the link between sub-optimal antenatal haemoglobin levels secondary to iron-deficiency anaemia and blood transfusion requirement after post-partum haemorrhage (PPH). Thus identifying whether patients are being managed correctly to optimise haemoglobin levels pre-delivery and assess whether blood transfusions are being used unnecessarily. Method: A retrospective audit was undertaken of 200 women in the Leeds Teaching Hospitals Trust (LTHT) who suffered a PPH of <1500 ml. The delivery suite register, Trust results server and transfusion database were used to check blood results at 28 weeks, 36 weeks/pre-partum and post-partum and identify those who received blood transfusions. Results: 24 women (12%) were anaemic during pregnancy – five at both 28 and 36 week/pre-partum checks. Nine of the 24 (37.5%) needed a blood transfusion following a PPH of <1500 mls. Of these nine, three missed the 36 week/pre-partum check, thus missing the last opportunity to identify and treat their anaemia. One of the nine transfused had no antenatal bloods taken at all. Conclusion: Effective management avoided the need for transfusion in 2/3 of the anaemic women. Yet failed in the remaining 1/3. Patient non-attendance, test refusal, and non-compliance with iron supplementation may be responsible for some transfusions, yet failure of health professionals to take bloods or act upon suboptimal results may account for the rest. Recommendations include using patient stickers in delivery registers to assist in data collection, increased patient education on the importance of appointment attendance and increased clinician/midwifery awareness on management of iron deficiency anaemia in pregnancy.